2017
DOI: 10.3897/afrinvertebr.58.21083
|View full text |Cite
|
Sign up to set email alerts
|

Edible insects of Northern Angola

Abstract: From 2013-2017, we accompanied and interviewed local people harvesting edible insects in the Northern Angolan province of Uíge. Insect and host plant samples were collected for species identification and nutritive analyses. Additionally, live caterpillars were taken to feed and keep until pupation and eclosion of the imago, necessary for morphological species identification. Altogether, 18 insect species eaten by humans were recorded. Twenty four edible insect species were formerly known from the country, four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The study also revealed that the average number of people per household of forest product vendors is 5.8 people. This result is higher than the general national average of 4.6 persons per household obtained in the general population and housing Angola's 2014 census conducted [26].…”
Section: A Socio-economic Profile Of Nwfp Sellersmentioning
confidence: 56%
See 1 more Smart Citation
“…The study also revealed that the average number of people per household of forest product vendors is 5.8 people. This result is higher than the general national average of 4.6 persons per household obtained in the general population and housing Angola's 2014 census conducted [26].…”
Section: A Socio-economic Profile Of Nwfp Sellersmentioning
confidence: 56%
“…The Uíge Province, located in the north of Angola, covers an area of 58,698 km2 and has a population of more than 1.4 million [26]. Uíge has a tropical savannah climate with a dry season (Sivu or Mbangala in the Kikongo language) [8] from May to September and annual rainfall of 900 to 1500 mm; the average annual temperature of the capital of Uíge is 23 °C [27], [28].…”
Section: A Description Of the Study Area And Selection Of Respondentsmentioning
confidence: 99%
“…According to Teffo et al [ 15 ], the consumption of insects in South Africa is more prevalent in Limpopo, Gauteng, North West, and Mpumalanga provinces. Across African countries, Zimbabwe [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], Angola [ 54 ], Tanzania [ 36 ], Nigeria [ 55 ], and Botswana [ 18 ] have been reported to consume edible insects. However, Ethiopia is one exception, because religious beliefs prohibit the consumption of insects, and only 1% of people interviewed were prepared to accept insects as a human food [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 Caterpillar Angola Larvae [ 96 ] Lepidoptera Notodontidae sp. 2 Caterpillar Angola Larvae [ 96 ] Lepidoptera Notodontidae sp. 3 Caterpillar Angola Larvae [ 96 ] Lepidoptera Notodontidae sp.…”
Section: Table A1mentioning
confidence: 99%
“…2 Caterpillar Angola Larvae [ 96 ] Lepidoptera Notodontidae sp. 3 Caterpillar Angola Larvae [ 96 ] Lepidoptera Notodontidae sp. 4 Caterpillar Angola Larvae [ 96 ] Lepidoptera Gastroplakaeis rubroanalis Caterpillar Angola Larvae [ 96 ] Lepidoptera Sciatta inconcisa Caterpillar Angola Larvae [ 96 ] Lepidoptera Elaphrodes lactea Gaede Caterpillar Democratic Republic of Congo Larvae [ 33 , 117 ] Lepidoptera Lobobunaea saturnus Fabricius Caterpillar Democratic Republic of Congo, Zimbabwe Larvae [ …”
Section: Table A1mentioning
confidence: 99%